Ownership Concentration and Firm Performance in Indonesia - Juanda Juanda (Journal of Accounting Research, Organization and Economics, 2018)
AbstractObjective – The study aim to investigate the effect of ownership concentration on the financial performance of firms listed in the Indonesian Stock Exchange from 2008 to 2012. Design/methodology – Data for the study were collected from the Indonesia Stock Exchange on or prior to 2 January 2008 and remain listed until 31 December 2012. The population is 140 industrial and manufacturing companies listed on the Indonesia Stock Exchange. But, there are only 43 companies meet the sampling criteria. To investigate the influence of ownership concentration on firm performance in Indonesia, multiple linear regression method was performed. Results – The results of this study is the ownership concentration positively and significantly influences firm performance in Indonesia and it acts as a substitute for shareholder protection. Research limitations/implications – The samples are only collected from manufacturing industry and does not take into account the shareholder identity. It is quite possible that shareholder identity influences the relationship between ownership concentration and firm performance. Therefore, future researchers are advised to take into account the shareholder identity so that it becomes clear whether shareholder identity indeed has an effect on such relationship.